Histone deacetylase 10-promoted autophagy as a druggable point of interference to improve the treatment response of advanced neuroblastomas - Oehme, Ina; Lodrini, Marco; Brady, Nathan; Witt, Olaf (Autophagy, 2013)
Neuroblastoma is the most common extracranial solid tumor in childhood. Despite intense multimodal therapy and many improvements through basic scientific and clinical research, the successful response of advanced-stage patients to chemotherapy remains poor. Autophagy is a cytoprotective mechanism that may help advanced cancer cells survive stressful conditions such as chemotherapy. Here we review our recent findings describing HDAC10 as a promoter of autophagy-mediated survival in neuroblastoma cells and identifying this HDAC isozyme as a druggable regulator of advanced-stage tumor cell survival. These results propose a new and promising way to considerably improve treatment response in the neuroblastoma patient subgroup with the poorest outcome.